2022
DOI: 10.3390/en15218196
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Investigation of the Effect of a Wind Turbine on the Atmospheric Boundary Layer

Abstract: Wind power engineering is one of the environmentally safe areas of energy and certainly makes a significant contribution to the fight against CO2 emissions. The study of the air masses movement in the zone of wind turbines and their influence on the boundary layer of the atmosphere is a fundamental basis for the efficient use of wind energy. The paper considers the theory of the movement of air masses in the rotation zone of a wind turbine, and presents an analytical review of applied methods for modeling the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…The data from meteorological observation towers and stations in Inner Mongolia and Hebei showed that the rates of change in the annual average wind speed and the average maximum wind speed after the completion of onshore wind farms were -1.5% and -18.5%, respectively, and the annual average wind speed showed a decreasing trend over time (Gu et al, 2016;Luo et al, 2021). The numerical model simulation results are similar, and the simulation results show a significant reduction in wind speed at the hub height level for onshore wind farms (Roy et al, 2004;Kovalnogov et al, 2022). In terms of the correlations between the timing of wind speed changes and seasonal distribution, the wind speed changes caused by onshore wind farms are mainly concentrated in spring and winter (14%), with a 10% reduction in daytime wind speeds and a 12% reduction in nighttime wind speeds (Gu et al, 2016;Liu et al, 2021b).…”
Section: Wind Speedmentioning
confidence: 87%
See 2 more Smart Citations
“…The data from meteorological observation towers and stations in Inner Mongolia and Hebei showed that the rates of change in the annual average wind speed and the average maximum wind speed after the completion of onshore wind farms were -1.5% and -18.5%, respectively, and the annual average wind speed showed a decreasing trend over time (Gu et al, 2016;Luo et al, 2021). The numerical model simulation results are similar, and the simulation results show a significant reduction in wind speed at the hub height level for onshore wind farms (Roy et al, 2004;Kovalnogov et al, 2022). In terms of the correlations between the timing of wind speed changes and seasonal distribution, the wind speed changes caused by onshore wind farms are mainly concentrated in spring and winter (14%), with a 10% reduction in daytime wind speeds and a 12% reduction in nighttime wind speeds (Gu et al, 2016;Liu et al, 2021b).…”
Section: Wind Speedmentioning
confidence: 87%
“…Numerical model simulation can theoretically analyze and predict the climatic effects caused by the construction and operation of onshore wind farms, and facilitate research on the related mechanisms. Currently, numerical model simulations of the ecological and climatic impacts of onshore wind farms mainly focus on the impacts generated by the wind turbines themselves, such as wind speed and turbulence (Roy et al, 2004; Fitch et al, 2013; Bleeg et al, 2018; Ai et al, 2022; Kovalnogov et al, 2022), although some studies have also analyzed near-surface temperatures and vegetation growth using numerical model simulations (Li et al, 2018). Overall, relatively few studies have used numerical model simulations to analyze the eco-climatic impacts of onshore wind farms, and the problem that needs to be solved lies in the further optimization of model parameters against a background that fully considers additional factors such as land-use types and local climatic conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las energías renovables son una solución al impacto ambiental negativo de los combustibles fósiles a nivel mundial, el número de trabajos de investigación relacionados indican una creciente preocupación por cambiar la producción energética a producción a partir de recurso renovable y así generar una disminución en el uso de sistemas energéticos contaminantes, actualmente existen trabajos que estudian el impacto de las turbinas en la zona en que son ubicadas (Bodini et al 2021) y otros sobre protección de las turbinas a temperaturas extremas (Kovalnogov et al 2022). Sin embargo, estudiar el torque generado por un aerogenerador ante cambios de temperatura mediante CFD resulta novedoso y aplicable a las etapas de diseño de parques eólicos.…”
Section: Introductionunclassified